Senegal: Recent developments in public agricultural research - Stads, Gert-Jan; Sène, Louis (International Food Policy Research Institute, 2010)
Public agricultural research and development (R&D) in Senegal has been negatively affected by contractions in funding and capacity since the mid-1980s. In 2008, the country employed 141 full-time equivalent (FTE) agricultural researchers and spent 6.5 billion CFA francs or 25.9 million PPP dollars on agricultural R&D (both in constant 2005 prices), which is well below the levels recorded in the 1980s and 1990s (Figure 1 and 2; Table 1). Unless otherwise stated, expenditures in this brief are expressed in purchasing power parity (PPP) prices. PPPs are synthetic exchange rates used to reflect the purchasing power of currencies; they typically compare prices among a broader range of goods and services than do conventional exchange rates.